The Nature of Human Creation in the Light of Islamic Education - Dora lathifa nurwachida; Fihris (Journal of Islamic Education Thought and Development, 2025)
This article examines the nature of human creation in the perspective of Islamic Education by using descriptive analytical research methods that are qualitative in nature. This research aims to understand the essence of human creation as a creature of Allah SWT and its relevance to the goals of Islamic education, namely to form people of faith, piety, and noble character. Data were collected through a literature study by referring to primary sources such as the Qur'an, Hadith, as well as classical and contemporary literature related to Islamic education and the philosophy of human creation. Data analysis was conducted critically and in-depth to explore fundamental concepts about human nature, the potential of reason and spirit, and human responsibility as khalifah fil ard. The results show that the nature of human creation in Islam is to fulfill the divine purpose, namely to worship Allah and maintain the harmony of the universe. Islamic education has a central role in actualizing the basic human potential (physical and spiritual) so that it is able to carry out its function as a servant and khalifah. This article concludes that a deep understanding of the nature of human creation is an important foundation in formulating an Islamic education paradigm that is holistic, integrative, and oriented towards Islamic character building. Thus, Islamic education does not only focus on intellectual aspects but also spiritual and moral.